Loss of microRNA-7a2 induces hypogonadotropic hypogonadism and infertility - Kashan Ahmed; Mary P. LaPierre; Emanuel Gasser; Rémy Denzler; Yinjie Yang; Thomas Rülicke; Jukka Kero; Mathieu Latreille; Markus Stoffel (AMER SOC CLINICAL INVESTIGATION INC, 2025)
MicroRNAs (miRNAs) are negative modulators of gene expression that fine-tune numerous biological processes. miRNA loss-of-function rarely results in highly penetrant phenotypes, but rather, influences cellular responses to physiologic and pathophysiologic stresses. Here, we have reported that a single member of the evolutionarily conserved miR-7 family, miR7a2, is essential for normal pituitary development and hypothalamic-pituitary-gonadal (HPG) function in adulthood. Genetic deletion of mir-7a2 causes infertility, with low levels of gonadotropic and sex steroid hormones, small testes or ovaries, impaired spermatogenesis, and lack of ovulation in male and female mice, respectively. We found that miR-7a2 is highly expressed in the pituitary, where it suppresses golgi glycoprotein 1 (GLG1) expression and downstream bone morphogenetic protein 4 (BMP4) signaling and also reduces expression of the prostaglandin F2a receptor negative regulator (PTGFRN), an inhibitor of prostaglandin signaling and follicle-stimulating hormone (FSH) and luteinizing hormone (LH) secretion. Our results reveal that miR-7a2 critically regulates sexual maturation and reproductive function by interconnecting miR-7 genomic circuits that regulate FSH and LH synthesis and secretion through their effects on pituitary prostaglandin and BMP4 signaling.